Rainfall Forecasting in the City of Pekanbaru Using the Exponential Smoothing Method - Rahmadeni, Rahmadeni; Desasri, Rifa; Safitri, Elfira (Indonesian Council of Premier Statistical Science, 2025)
Rainfall is one of the main components in the climate system that has a major influence on various sectors, such as agriculture, transportation, and disaster management. The city of Pekanbaru in Riau Province has tropical climate characteristics with varying levels of rainfall throughout the year. Therefore, a forecasting method is needed that is able to accurately predict rainfall. This study aims to identify the most suitable forecasting model for rainfall data in the region. The two methods used in this study are Single Exponential Smoothing (SES) and Holt's Double Exponential Smoothing (DES). The results of the analysis showed that the SES method provided a higher level of accuracy compared to the DES Holt method, with a MAPE value of 33.37%. Thus, the SES model is considered the best method in predicting rainfall in the city of Pekanbaru.